5-HT1A C-1019G (rs6295) Predicts Aripiprazole Treatment Response Specifically for Cognitive and Depressive Symptoms in Schizophrenia. Issue 1 (February 2017) - Chen, Shih-Fen; Shen, Yu-Chih
Abstract : Supplemental digital content is available in the text.